2022
DOI: 10.3389/fpsyg.2022.884520
|View full text |Cite
|
Sign up to set email alerts
|

Single-Item Happiness Measure Features Adequate Validity Among Adolescents

Abstract: BackgroundHappiness is becoming increasingly relevant in recent research, including adolescents. Many studies are using the single-item measure for adolescent happiness, however, its validity is not well known. We aimed to examine the validity of this measure among adolescents in three countries from distinct European regions – Eastern (Lithuania), Southern (Portugal), and Western (Scotland).Materials and MethodsThe analysis included data from Health Behaviour in School-aged Children (HBSC) study from three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…In particular, the single-item demonstrated good concurrent validity with measures of happiness and life satisfaction, convergent validity with optimism and positive affect, and divergent validity with measures of anxiety and negative affect. Lukoševičiūtė et al [ 39 ] also found adequate support for the use of a single-item happiness measure among adolescents across three European regions. The 2020 GYC originally wrote their own happiness item, and the University partners brought in this single-item question as a possible alternative.…”
Section: Methodsmentioning
confidence: 98%
“…In particular, the single-item demonstrated good concurrent validity with measures of happiness and life satisfaction, convergent validity with optimism and positive affect, and divergent validity with measures of anxiety and negative affect. Lukoševičiūtė et al [ 39 ] also found adequate support for the use of a single-item happiness measure among adolescents across three European regions. The 2020 GYC originally wrote their own happiness item, and the University partners brought in this single-item question as a possible alternative.…”
Section: Methodsmentioning
confidence: 98%
“…It can be described as a warm, positive, and joyful feeling that often arises in response to positive life events such as success, love, or personal growth [32]. Happiness can also be experienced as a more general sense of well-being and satisfaction with life [33]. The feeling of happiness differs from one person to another even though they are in the same situation [34].…”
Section: Students' Feeling Of Happiness and Mental Health During Covi...mentioning
confidence: 99%